Randomized Controlled Trial Study of the Impact of a Spiritual Intervention on Hope and Spiritual Well-Being of Persons with Cancer - Afrasiabifar, Ardashir; Mosavi, Asadollah; Jahromi, Abolfazl Taghipour; Hosseini, Nazafarin (Investigación y Educación en Enfermería, 2021)
Objective. To determine the impact of spiritual intervention on hope and spiritual well-being of persons with cancer Methods. Randomized controlled trial in which 74 patients with cancer referring to a chemotherapy ward of Shahid Rajaie Hospital in Yasuj city, Iran, were participated. The eligible patients were randomly assigned to either intervention or control group. Spiritual-based intervention was performed based on the protocol in four main fields namely; religious, existence, emotional and social over 5 sessions before chemotherapy.The participants in the control group had received usual cares .Data were collected using Snyder’s Hope Scale and Ellison’s Scale Spiritual Well-Being Scale on a week before and after intervention. Results. The total mean scores of the scales of hope and spiritual well-being in both groups did not present statistical differences in the pre-intervention assessment. In contrast, at the post assessment, significant differences (p<0.001) were found in the mean scores between the intervention and control groups on the hope scale (60.9 versus 39.8) and on the spiritual well-being scale (94.3 versus 71.6). Conclusion. Spiritual intervention could promote hope and spiritual well-being of persons with cancer.